Emotional excitability and behaviour of horses in response to stroking various regions of the body. (28th August 2018) - Janczarek, Iwona; Stachurska, Anna; Wilk, Izabela; Krakowski, Leszek; Przetacznik, Monika; Zastrzeżyńska, Monika; Kuna‐Broniowska, Izabela
Abstract: Touching the skin by gentle stroking is frequently used to reward horses. The objective of the study was to examine emotional excitability and behaviour of horses in response to stroking different regions of their bodies. The study included 15 adult warmbloods and 15 adult ponies, nine geldings and six mares within each type of horse. First, a novel‐object test was conducted. For five successive days, one of five regions of the horse's body was stroked on each side for 5 min. Heart rate and heart rate variability were monitored at rest, during the test and stroking. Simultaneously, horse behaviour was assessed on a 1–5 scale. The data were analysed using analysis of variance GLM, Tukey's Honestly Significant Difference test and Spearman's correlation coefficient. When stroked, horses were more excited than when at rest. Differences in emotional excitability and behaviour while stroking various body regions depended on the type and sex of horses. Parameters studied indicated that both in warmbloods and ponies, stroking the head may be beneficial, whereas the trunk should be treated with caution. Stroking may have a more positive influence in horses of lower emotionality and highly estimated behaviour at rest and during the novel‐object test.